1991
DOI: 10.21273/hortsci.26.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Nutsedge Control in Landscape Plants

Abstract: Preplant-incorporated, preemergence, and postemergence herbicides were evaluated for yellow nutsedge (Cyperus esculentus L.) control and for phytotoxicity to four container-grown woody plants. Preplant-incorporated or preemergence applications of chlorimuron at 0.07 kg a.i./ha or imazaquin at 1.12 kg a.i./ha provided the greatest control of yellow nutsedge. Imazaquin applied at 0.28, 0.56, 0.84, or 1.12 kg a.i./ha suppressed growth of Rhododendron ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
7
2
Order By: Relevance
“…In previous research (7,12), chlorimuron and imaza quin applied POST generally provided lower control than that observed in this study, although the reported results on yellow nutsedge control with chlorimuron were variable. Pyridate controlled yellow nutsedge shoots, but regrowth occurred two to three WAT (6), similar to the results seen in the current study.…”
Section: Flurtamone and Pyridate Visibly Injured Compacta Holly Barbcontrasting
confidence: 86%
See 1 more Smart Citation
“…In previous research (7,12), chlorimuron and imaza quin applied POST generally provided lower control than that observed in this study, although the reported results on yellow nutsedge control with chlorimuron were variable. Pyridate controlled yellow nutsedge shoots, but regrowth occurred two to three WAT (6), similar to the results seen in the current study.…”
Section: Flurtamone and Pyridate Visibly Injured Compacta Holly Barbcontrasting
confidence: 86%
“…Pyridate at either rate did not affect yellow nutsedge shoot weight, whereas only the higher rate of flurtamone reduced yellow nutsedge shoot growth. In previous research, imazaquin, imazethapyr, and chlorimuron ap plied PRE controlled yellow nutspdge > 75% (7,12), which is greater control than that observed in this research. a For PRE and POST treatments, the plants were cut back to the soil line 8 WAT, and regrowth shoot dry weight was recorded 12 WAT.…”
Section: Flurtamone and Pyridate Visibly Injured Compacta Holly Barbcontrasting
confidence: 57%
“…A single tuber of yellow nutsedge is capable of producing about 7000 new tubers and 1900 new aerial shoots in one season (Tumblesome and Kommedahl, 1961). Cultivation or mechanical removal of yellow nutsedge often leads to spreading the tubers throughout the nursery and is therefore an ineffective control method (Wilcut et al, 1991). Container studies have demonstrated effective yellow nutsedge control using rates of bentazon, a benzothiadiazole, from 1.5 to 6.0 lb/ acre (1.68 to 6.72 kg•ha -1 ) (Fretz and Sheppard, 1978).…”
Section: Postemergence Weed Control Grass-active Herbicidesmentioning
confidence: 99%
“…Yellow and purple nutsedges are difficult weeds to control worldwide (Holm et al 1991), and cause severe economic loss in both agronomic and horticultural crops (Bingham 1977;Holm et al 1991;Keeley 1987;Stoller 1981;Tweedy et al 1975;Wilcut et al 1991). Both species were not considered to be serious weed problems until the 1960s (Bell et al 1962); however, enormous opportunities for nutsedge interference were created with the advent of selective herbicides (Keeley 1987).…”
Section: Introductionmentioning
confidence: 99%